Disintegration of social cognitive processes in schizophrenia - Karakuła, Hanna; Krukow, Paweł; Kalinowska, Joanna; Stelmach, Ewa; Kowal-Popczak, Agnieszka (Psychiatria polska, 2013)
Despite rapid development of research on social cognition (SC) impairments in schizophrenia, efforts are still made to generate new, broader theoretical models which include the neural network approach to those dysfunctions. The aim of this study was the evaluation of the structure of SC in patients with schizophrenia in comparison to healthy subjects. The studied groups consisted of 55 subjects: 30 patients with paranoid schizophrenia according to DSM-IV criteria, and 25 control healthy subjects matched for age, gender and education to the clinical group. In order to assess processes of SC, a battery of tests was administered: Theory of Mind Picture Stories to assess theory of mind, trials "Faces" (from Ekman and Friesen's set of emotional expressions) and "Figures" (from the publication by Argyle) to evaluate recognition of emotions from facial and gesture expression. The methods included also an assessment of self-criticism (insight) relating to the subject's processes of SC. The level of efficacy of SC was lower in the patients compared to the controls. In the clinical group, theory of mind was the most important factor for the overall level of SC and its impairments. There was inadequate, decreased patients' self-criticism regarding their execution of SC tests. The insight did not correlate with any other SC variables in the clinical group. In general, the group characterized by lower integration of social cognitive processes, also obtained lower scores in individual dimensions of SC. The structure of social cognitive processes in schizophrenic group, unlike in healthy subjects, shows characteristics of generalized disintegration.